Teacher Staffing Challenges in California: Examining the Uniqueness of Rural School Districts - Dan Goldhaber; Katharine O. Strunk; Nate Brown; Natsumi Naito; Malcolm Wolff (SAGE Publishing, 2020)
Using unique data from California on teacher job vacancies, we investigate staffing challenges across the urbanicity spectrum, focusing on the extent to which the characteristics of rural school systems explain the differences in staffing challenges as measured by vacancy rates and emergency credentialed teachers, relative to other urbanicities. We find that rural districts have significantly and substantially higher staffing challenges than districts from different urbanicity classifications (urban, suburban, and towns). Some of these differences are explained by district-level attributes, such as the proportion of students in poverty in the district. The geography of rural districts itself also explains the high levels of staffing challenge as rural districts are more likely to be located on a state border and far from teacher education programs, both of which are strongly associated with staffing challenge measures. Even after controlling for a rich set of observable covariates, there is evidence that rural districts are still somewhat more likely to face staffing challenges, suggesting that there are unobserved aspects of being rural associated with the desirability of employment that are not readily captured by quantitative data.